The Nature of Ottoman-Acheh Relations in the 16th and 17th Centuries: Commercial, Religious and Military Connections - Alatas, Sharifah Munirah (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Nature of Ottoman-Acheh Relations in the 16th and 17th Centuries: Commercial, Religious and Military Connections